2017
DOI: 10.3141/2662-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Crowdsourced Near-Miss and Collision Cycling Data and Official Bike Safety Reporting

Abstract: Official sources of cyclist safety data suffer from underreporting and bias. Crowdsourced safety data have the potential to supplement official sources and to provide new data on near-miss incidents. BikeMaps.org is a global online mapping tool that allows cyclists to record the location and details of near misses and collisions they experience. However, little is known about how the characteristics of near-miss and collision events compare. Further, the question remains whether the characteristics of crowdsou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The gender breakdown from BikeMaps.org data used in this current analysis is presented by city in Table 2. A study of reports on BikeMaps.org from Metro Vancouver found that gender and age were not associated with the reporting of collisions relative to near misses (Branion-Calles et al, 2017). It should be noted that while cities usually have official bicycling crash data, access and completeness varies greatly across Canadian jurisdictions.…”
Section: Bikemapsorg Incident Self-reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gender breakdown from BikeMaps.org data used in this current analysis is presented by city in Table 2. A study of reports on BikeMaps.org from Metro Vancouver found that gender and age were not associated with the reporting of collisions relative to near misses (Branion-Calles et al, 2017). It should be noted that while cities usually have official bicycling crash data, access and completeness varies greatly across Canadian jurisdictions.…”
Section: Bikemapsorg Incident Self-reportsmentioning
confidence: 99%
“…Evaluation of reports shows that there are some consistent differences between conditions that lead to near miss reporting, relative to collision reports. Data show that a higher odds of near miss reports are associated with commute trips, incidents involving motor vehicles, and in locations without bicycle-specific facilities (Branion-Calles et al, 2017). It is also true that the exact nature of what is reported as a near miss will vary, especially depending on the experience of the bicyclists.…”
Section: Bikemapsorg Incident Self-reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we refer to visual conditions as the significant changes in the appearance of cities during dawn/dusk, day or night-time including the effect of glare on visibility, whereas weather conditions are the meteorological changes of the represent crucial factors for many urban studies including transport, behaviour, and safety-related research [5]. For example, walking, cycling, or driving in rainy weather is associated with a higher risk of experiencing an incident than in clear weather [5,6]. Fog, snow, and glare have also been found to increase risk [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, walking, cycling, or driving in rainy weather is associated with a higher risk of experiencing an incident than in clear weather [5,6]. Fog, snow, and glare have also been found to increase risk [6,7]. Importantly, it is not only the inherent risk that different weather and visual conditions pose to human life that is of interest to researchers.…”
mentioning
confidence: 99%